Residential Air Conditioning System Integrated with Packed Bed Cool Storage Unit for Promoting Rooftop Solar PV Power Generation - Kesavan Muthaiyan; Rajamani Narayanasamy; Chidambaram Lakshmanan; Pandiyarajan Vellaichamy; Velraj Ramalingam (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The increase in the share of renewable-based power in the gross power generation in most countries causes significant concerns over the addition of renewable power with the grid, results in stability issues in most developed nations. Energy storage is an emerging technology that is considered the ultimate solution in developing microgrids with distributed renewable power generation. The cool thermal storage plays a vital role in economically promoting renewable power among different storage units. The major objective of the research work is to demonstrate the integration of residential air-conditioning systems with packed bed cool storage units to promote rooftop solar power generation for residential space cooling applications. In order to achieve the said objective, an experimental investigation was made to study the charging/discharging characteristics of a packed bed cool-storage unit combined with a chiller and a cooling coil unit suitable for small capacity air-conditioning applications. The system consists of encapsulated spherical capsules filled with a phase change material blended with distilled water and pseudomonas (nucleating agent) and the heat transfer fluid as a combination of distilled water and Mono-ethylene glycol. A cooling coil unit was connected to the cool-storage tank to transfer cool energy from the storage tank to the space to be cooled when there is a demand. The important parameters, such as instantaneous and cumulative heat transfer during the charging/discharging processes, are presented. The average COP values of the chiller during the charging operation were estimated as 1, 0.93, and 0.89 when the HTF setpoint temperatures were -6°C, -9°C, and -12°C, which shows a decrease in performance as the setpoint temperature decreases. During the discharging process, a cooling load of 2.25 kW is obtained during the first cycle of operation and gradually reduces to 0.3 kW during the sixth cycle of operation. The increase in the HTF temperature during each cycle of operation indicates that the Phase Change Material (PCM) in the balls cannot release the heat as per the demand after a certain period of discharging. Hence, decreasing the internal thermal resistance by suitable measures is essential to achieve uniform heat flux and to operate the system successfully